2021
DOI: 10.1016/s0140-6736(21)02555-1
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of self-isolation among contacts of cases of COVID-19: a national telephone survey in Wales

Abstract: Background Self-isolation is known to be challenging and adherence is dependent on a range of psychological, social, and economic factors. We aimed to identify the specific challenges experienced by contacts of COVID-19 cases to better target support and minimise the harms of self-isolation. MethodsThe Contact Adherence Behavioural Insights Study (CABINS) was a 15 min telephone survey of contacts of COVID-19 cases, identified through NHS Wales Test Trace Protect (TTP). Quota sampling by age, gender (interlocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Isherwood et al 31 found, in Wales, "Self-isolation is particularly challenging for younger people, women and those with precarious incomes". As with our study, they found a barrier to self-isolation was wanting to see family and friends.…”
Section: Discussionmentioning
confidence: 99%
“…Isherwood et al 31 found, in Wales, "Self-isolation is particularly challenging for younger people, women and those with precarious incomes". As with our study, they found a barrier to self-isolation was wanting to see family and friends.…”
Section: Discussionmentioning
confidence: 99%
“…Isherwood et al [40] found, in Wales, “Self-isolation is particularly challenging for younger people, women and those with precarious incomes”. As with our study, they found a barrier to self-isolation was wanting to see family and friends.…”
Section: Discussionmentioning
confidence: 99%
“… Alle and Berntsen (2021) suggested that isolation can lead to an increased risk of psychosis in residents. Isherwood et al (2021) analyzed the psychological impact of isolation on residents during the COVID-19 pandemic through a telephone survey. Gierveld et al (2018) analyzed that loneliness caused by isolation can have adverse effects on people’s physical resistance.…”
Section: Introductionmentioning
confidence: 99%